2017
DOI: 10.21037/atm.2017.06.60
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and prognosis—review of biomarkers for mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive disease arising in pleural cell lining and is associated with asbestos exposure. Today, there is a rising incidence of MPM reaching 3,000 annual cases nationally, primarily from the large population occupationally exposed to asbestos between 1940 and 1980. With a prolonged latency period, presenting clinically 10 to 40 years after exposure, MPM is often diagnosed in late stages and presents median survival time of less than 12 months. There is a serious nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 69 publications
1
54
0
Order By: Relevance
“…On the other hand, some other studies suggested that plasma fibulin-3 levels have low diagnostic accuracy [48][49][50]. The study of Creaney et al identified soluble mesothelin as a superior diagnostic biomarker for MM compared to fibulin-3, whereas fibulin-3 provided superior prognostic information compared to mesothelin [48].…”
Section: Fibulinmentioning
confidence: 99%
“…On the other hand, some other studies suggested that plasma fibulin-3 levels have low diagnostic accuracy [48][49][50]. The study of Creaney et al identified soluble mesothelin as a superior diagnostic biomarker for MM compared to fibulin-3, whereas fibulin-3 provided superior prognostic information compared to mesothelin [48].…”
Section: Fibulinmentioning
confidence: 99%
“…and Sun et al, groups from the University of Hawaii Cancer Center and NYU Langone Medical Center (50,51). The authors listed the most promising markers associated with diagnosis and prognosis of MPM in the current research field.…”
Section: Pathological and Molecular Prognostic Factorsmentioning
confidence: 99%
“…In summary, while all of these markers showed promising results, most have yet to be independently and prospectively validated, and for some of them controversial results from different studies concerning their prognostic impact need to be addressed (51). So far, all these above-mentioned markers and their potential prognostic value have no impact in patient selection, but may be included in selection algorithms alongside with clinical markers in prognostic scores.…”
Section: Pathological and Molecular Prognostic Factorsmentioning
confidence: 99%
“…Other possible regions affected by this disease are the peritoneum, the pericardium and the tunica of testis and ovary (Bridda, Padoan, Mencarelli, & Frego, 2007). Although rare, with around 3,000 new patients diagnosed each year alone in the United States (Sun, Vaynblat, & Pass, 2017), it is considered a very aggressive and deadly form of cancer (Carbone et al, 2019).…”
Section: Introductionmentioning
confidence: 99%